Prerequisites for the development of “green” entrepreneurship in Kazakhstan - Nurmaganbetov, A.; Shakeev, S.; Serikbayeva, B. (BUKETOV BUSINESS REVIEW, 2024)
Object: based on the analysis of the current state of affairs in the field of industrial development, entrepreneurship, and environmental protection, to establish prospects for the development of “green” entrepreneurship in Kazakhstan. Methods: statistical-economic, dialectical, comparative methods, abstraction method, generalization method, general formal logical methods such as classification, analysis, synthesis, deduction, induction. Findings: based on the analysis of the theoretical base and conceptual apparatus, the definition of “green” entrepreneurship was established, it was established that in large cities of Kazakhstan the air condition is extremely polluted and harmful to human health, the Kazakh experience in the development of “green” entrepreneurship was studied, “weaknesses” and negative examples of the implementation of projects in the field of “green” economy were identified In Kazakhstan, as a result of the analysis of domestic and international experience, four main promising directions for the development of “green” entrepreneurship in Kazakhstan were identified. Conclusions: taking into account the world experience, as well as the state of the ambient air in large cities of Kazakhstan, the vector of sustainable development and improvement of the environmental situation, the driver of the development of a green economy in Kazakhstan should use the advantages of “green” entrepreneurship, especially in the transport sector, green construction, the development of innovative production and the circular economy.